CHARACTERISTICS OF ENTREPRENEURSHIP AND ENTREPRENEURIAL MOTIVATION ON BUSINESS SUCCESS AT STREET VENDORS AT AL-AKBAR MOSQUE SURABAYA - Siti Samsiyah; Bisma Arianto; Bebyta Putri Hendriyanti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This research was conducted with the aim of knowing the effect of entrepreneur characteristics and motivation on business success for street vendors around Al-Akbar Surabaya Mosque. The sample in this study amounted to 127 respondents, non probability sampling method was applied, and the sample type is purposive sampling using the slovin formula. The method of research by quatitative techniques using multiple linear regression analysis techniques. The characteristics of entrepreneurship partially positively and significantly affect the success of the business obtained a count value of 2,951 with a significant value of 0.004. Furthermore, entrepreneurship motivation partially positively and significantly affects the success of the business to obtain a count value of 6,670 with a significant value of 0.000. After that, in the results of the F test it is known that the characteristics of entrepreneurship and entrepreneurship motivation simultaneously have a positive and significant effect on the success of the business Keywords : Characteristics of Entrepreneurship, Motivation, and Business Success